Effects of extraction, purification and freeze drying conditions on enzymatic properties of serine protease from mango (Mangifera Indica L. Cv.Chokanan) peel - Amid, Mehrnoush (2011)
This research studies the extraction, purification, characterization and preservation by freeze drying of serine protease from mango (Mangifera Indica CV. Chokanan) peel. Serine protease is one of the most important enzymes widely used in biotechnological and industrial applications. The purification was carried out using expanded bed adsorption (EBA) and aqueous two-phase system (ATPS). In addition, the main factors affecting enzymatic properties of serine protease were optimized using response surface methodology (RSM). It was found that the optimum condition for serine protease extraction was an amount of 50 ml of sodium phosphate buffer at 2.5 °C for 2min. Also, the specific activity of enzyme after extraction was 17.2 U/mg. In continuing experiments the optimal conditions of purification using EBA were proved to be sample load, washing and elution at flow rate of 100 cm/h and pH 7.5. In addition, heat treatment of unclarified feedstock was found to be an important parameter in decreasing the level of the adsorbed contaminated protein. It was demonstrated that serine protease could be recovered with a purification factor of 11.39 and a yield of 82%, using EBA. Results indicated that EBA is a suitable method that allows recovery of serine protease to be achieved without product loss. Mango peel contains a lot of fiber that needs filtration for recovery with EBA, which is time consuming and costly, so the purification of serine protease was also studied with ATPS polyethylene glycol/ potassium phosphate. The optimum purification factor and yield were obtained when 6000 g/mol of polyethylene glycol, 28.5% (w/w) of tie light length and 5% of NaCl were used. Serine protease purification factor and yield using ATPS were 12.51 and 89%, respectively. Purification with ATPS does not need filtration and thus, this method is more economical, faster and with easy scale up compared to EBA. Yield of serine protease after using freeze drying in the presence of coating agents and activator was increased to 92.2%. The optimum temperature and pH for activity of serine protease were 70°C and 8, respectively. This enzyme was also stable in the presence of inhibitors, surfactants and oxidizing agents. It was additionally found that activity of serine protease was increased in the presence of calcium ions.